Effectiveness of sodium bicarbonate infusion on mortality for elderly septic patients with acute metabolic acidosis - Huang, Sai; Peng, Yaojun; Wang, Lili; Wang, Jing; Zhou, Xuan; Cui, Xiang; Chen, Li; Yang, Bo; Feng, Cong (Frontiers in Pharmacology, 2022)
Objective: This study aimed to explore the effectiveness of sodium bicarbonate (SB) infusion on mortality in elderly septic patients with acute metabolic acidosis (MA) and in other subgroups. Methods: Retrospective analysis of a large ICU database (MIMIC-IV) was performed. Elderly septic patients with acute MA were identified from MIMIC-IV. Propensity score analysis (PSA) was performed to explain for the baseline differences in the probability to receive SB or not. The marginal structural Cox model (MSCM) was developed to adjust for both baseline and time-varying confounding variables. The primary outcome was the ICU and hospital mortality. Results: A total of 869 elderly septic patients with acute MA were identified in this study, including 361 in the SB group and 508 in the non-SB group. In the PSA, SB infusion was not associated with reduced ICU (HR 0.82, 95% CI 0.62–1.10; p = 0.19) or hospital (HR 0.94, 95% CI 0.74–1.19; p = 0.60) mortality in overall elderly septic patients with acute MA. In the subgroup of severe metabolic acidosis, SB infusion could not improve the ICU (HR 0.82, 95% CI 0.62–1.10; p =0.19) and hospital (HR 0.94, 95% CI 0.74–1.19; p =0.60) mortality on elderly septic patients. However, In the subgroup of moderate metabolic acidosis, SB infusion could be found associated with improved ICU (HR 0.64, 95% CI 0.43–0.95; p <0.05) and hospital (HR 0.70, 95% CI 0.50–0.99; p <0.05) survival in elderly septic patients. In the MSCM, the results were similar with PSA. Conclusion: SB infusion could improve both ICU and hospital survival for elderly septic patients with acute metabolic acidosis.